O atendimento da educação infantil em contextos rurais: problematizando o assunto - MARGALHO, Franciléia Sardinha (2023)
The article deals with the attendance of Early Childhood Education in the Field, in the municipality of AbaetetubaPA. Thus, the study aimed to understand the education of children in rural areas, elucidating educational policy and the development of the teaching-learning process at this level of teaching. For this, we took as a methodological path the bibliographical research, added to our experience as a teacher in these contexts and in this city. References were helpful authors, such as Gomes (2009), Kuhlmann Jr (1998), Oliveira (2002), in addition to legislation that cover the theme of Rural Education, Early Childhood Education in the Countryside and Education Childish. From the study, we can say that we have an educational policy that says specificity of Early Childhood Education in the Field, but learning and educational practices need to be consistent with the needs of the children of the passing countryside, among others factors, by teacher training (initial and continuing) for this school phase as a factor fundamental. This, if we continue desires of an education of children in their infancy from/in field.